Strengthening of Indonesian Cultural Literacy for Students of Osaka University of Japan through Traditional Arts and Sports Based on Local Wisdom - Andriyanto, Octo Dendy; Nurhadi, Didik; Arief, Nur Ahmad; Wijaya, Andhega; Sukarman; Mael, Masilva Raynox; Vientiani, Cynthia (Jurnal Soeropati, 2024)
This study aims to introduce and promote Indonesian arts and culture at the Graduate School of Humanities, Indonesian Foreign Studies, Osaka University, Japan. The high interest in learning the Indonesian language at Osaka University requires strong support in the aspects of arts, culture, and even traditional sports to enrich knowledge of Indonesian local wisdom. Strengthening cultural literacy through traditional arts and sports emphasizes the values of local wisdom, particularly solidarity, mutual cooperation (gotong royong), honesty, as well as mental and physical health for Osaka University students through Indonesian cultural learning. This activity employs the Empowerment-Based Research (EBR) method, starting from identifying problems, designing activities, evaluation, and dissemination. As a result, students and lecturers from the Graduate School of Humanities, Indonesian Foreign Studies at Osaka University actively participated in the designed training sessions. These trainings focused on introducing dining etiquette, traditional herbal drinks (jamu), traditional music with angklung, and traditional sports such as Patil Lele and Gobag Sodor. Through this training, the aim is not only to teach the materials but also to highlight cultural values and local wisdom as part of cultural diplomacy.